Optimised placement of control and protective devices in electric distribution systems through reactive tabu search algorithm - da Silva, Luis G. Wesz [UNESP]; Pereira, Rodrigo A. Fernandes [UNESP]; Abbad, Juan Rivier; Mantovani, Jose R. Sanches [UNESP] (Elsevier B.V. Sa, 2008)
Optimised placement of control and protective devices in distribution networks allows for a better operation and improvement of the reliability indices of the system. Control devices (used to reconfigure the feeders) are placed in distribution networks to obtain an optimal operation strategy to facilitate power supply restoration in the case of a contingency. Protective devices (used to isolate faults) are placed in distribution systems to improve the reliability and continuity of the power supply, significantly reducing the impacts that a fault can have in terms of customer outages, and the time needed for fault location and system restoration. This paper presents a novel technique to optimally place both control and protective devices in the same optimisation process on radial distribution feeders. The problem is modelled through mixed integer non-linear programming (MINLP) with real and binary variables. The reactive tabu search algorithm (RTS) is proposed to solve this problem. Results and optimised strategies for placing control and protective devices considering a practical feeder are presented. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: network protection systems; restoration; reliability; reactive tabu search